Engineered Schwann Cell-Based Therapies for Injury Peripheral Nerve Reconstruction - Su, Qisong; Nasser, Moussa Ide; He, Jiaming; Deng, Gang; Ouyang, Qing; Zhuang, Donglin; Deng, Yuzhi; Hu, Haoyun; Liu, Nanbo; Li, Zhetao; Zhu, Ping; Li, Ge (Frontiers in Cellular Neuroscience, 2022)
Compared with central nervous system, the adult peripheral nervous system has a remarkable regenerative capacity, which is due to strong plasticity of Schwann cells in peripheral nerves. After peripheral nervous injury, Schwann cells dedifferentiate and transform into repair phenotypes, playing a critical role in axonal regeneration, myelin formation, and clearance of axonal and myelin debris. In view of the limited self-repair ability of Schwann cells for long segment defect of peripheral nerve defects, it is of great clinical value to supplement Schwann cells in necrotic areas through gene modification or stem cell transplantation, or to construct tissue-engineered nerve combined with bioactive scaffolds to repair tissue defects.Based on the developmental lineage of Schwann cells and the gene regulation network after peripheral nerve injury, this review summarize the possibility of using Schwann cells constructed by the latest gene modification technology to repair peripheral nervous injury. The therapeutic effect of tissue-engineered nerve constructed by materials combined with Schwann cells is more similar to autologous transplantation which is the gold standard for peripheral nerve injury repair. Therefore, this review generalize the research progress of biomaterials combined with Schwann cells for peripheral nerve injury repair. Based on the difficulty of donor sources, this review also discuss the potential of "unlimited" provision of pluripotent stem cells capable of directed differentiation or transforming existing somatic cells into induced Schwann cells. The summary of these concepts and therapeutic strategies makes it possible for Schwann cells to be used more effectively in the repair of peripheral nervous system injury.